Tingkat Keberlanjutan Pemanfaatan Ruang Publik Multifungsi di Permukiman Kumuh - Violla Caesandra; Hanny Wahidin Wiranegara; Sugihartoyo Sugihartoyo (TATALOKA, 2020)
Due to the limitation of slum dweller’s residence, they use public spaces for their daily activities. One kind of them  is a park. Public space used for various kinds of activities by slum dwellers is called a multifunction public space. Utilization of multifunction public space can potentially lead to spatial use conflict which interfere with its functional sustainability. The aim of this research was to identify the level of sustainability of the utilization of a multifunction public space in the slum area. This research used a quantitative approach and a questionnaires survey method. Respondents were slum dwellers using the park. The total respondents was 96 by using the Lemeshow formula. The results showed that there were differences in the level of sustainability among three parks. The highest level of sustainable utilization is Pendongkelan, the medium level is Melati Indah, and the lowest level is Taman Anggrek. There were four aspects of sustainability which were measured. Diversity and harmony were two aspects determining sustainability. For sustainability of spatial utilization of the multifunction public space in the slum area need management to take care of the size of the park, the availability of park amenities, and its accessibility.